Is there a new Brazilian development model? - Michael MacLennan; Armando Barrientos; Edmund Amann (International Policy Centre for Inclusive Growth (IPC-IG), 2015)
As the world begins to wake up to the dire social and economic consequences of rising inequality, we must recognise that it is not an inevitable side-effect of economic growth and development. Many Latin American countries, and Brazil in particular, have demonstrated it is possible to achieve inclusive growth, which has reduced inequality and poverty. Despite its current difficulties, Brazil offers a striking example of inclusive growth. Inequality has fallen sharply over the past decade and a half, a period which has also seen the country lift an estimated 40 million people out of poverty. Although growth rates have been modest in comparison to China or India, Brazil has implemented a raft of measures to ensure the results of such growth have been shared throughout society. While Brazilians have seen their incomes rise, the poorest have benefited most. The growth experienced by Brazil hasn't simply been attained through the unsustainable exploitation of natural resources. Despite serious lingering problems, deforestation rates in the Amazon have fallen remarkably since 2004. New jobs have been created, child mortality has plummeted, and schooling rates have increased. So how have these gains been achieved, are they sustainable, what challenges remain, and what can other developing countries learn from Brazil's experiences? These were the questions asked by a team of researchers from Brazil, Europe and the USA who formed the International Research Initiative on Brazil and Africa (IRIBA). This issue of Policy in Focus looks at the findings and insights they have produced. The foundations of Brazilian progress can be traced back to the transition from a dictatorship to a democracy in the mid-1980s and the vision for the country which emerged. A firm consensus between citizens and politicians to address the "social debt" created by soaring inequality set the country on a new path. After the economy was stabilised in the mid-1990s, the economic management pursued by successive governments enabled innovative social policies to flourish. As a more inclusive and prosperous Brazil has developed, the public demand for further progress has also grown. The large protests surrounding the 2014 Football World Cup, worries about an economy mired in recession, and deep concern with serious corruption scandals demonstrate that the Brazilian consensus is under considerable strain. [...]
Keywords: 330; Brazil; development